Financial Literacy and Its Implications for Business Sustainability of Young Entrepreneurs - Tia Yuliawati; Netti Siska Nurhayati; Annisa Ciptagustia; Asep Miftahuddin (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
One of the focuses of the Sustainable Development Goals is to create decent work and economic growth (Decent Work and Economic Growth), which is to promote sustainable and inclusive economic growth, employment and decent work for all. One of the big challenges for the Indonesian people is the burden of unemployment as a result of the narrowing of job opportunities. Concrete efforts are needed so that the number of unemployed can be reduced, one of which is through increasing the number of entrepreneurs in Indonesia. However, the data shows that almost 90% of startups in Indonesia end up in failure due to low financial literacy which has an impact on poor financial behavior. This study was conducted to examine the effect of financial literacy on business sustainability with financial behavior as a mediating variable. This study uses a quantitative approach with descriptive verification method. The analysis technique that will be used is SEM (Structural Equation Modeling) analysis with the help of SmartPLS 4.0 software. The research respondents were young entrepreneurs from the Universitas Pendidikan Indonesia (UPI) students represented by UPI students who are members of the Himpunan Pengusaha Muda Indonesia (HIPMI) PT UPI with a total of 96 respondents. The results show that the type of mediation that occurs in this study is